Pengaruh Green Accounting dan Kinerja Lingkungan terhadap Nilai Perusahaan pada Perusahaan Manufaktur - Kadek Supadi; Ni Made Intan Priliandani; Ni Made Rai Juniariani (UNHI Press, 2026)
Abstract: The increasing attention to sustainability issues and the fluctuations in the value of manufacturing companies, despite their continued growth in contribution to the national economy, has led to increased concern. This quantitative study examines how green accounting and environmental performance influence company value among 76 manufacturing firms on the IDX in 2024. Using multiple regression, findings reveal that green accounting holds no significant impact on firm value (p=0.573). Conversely, environmental performance demonstrates a strong positive effect (p=0.000), suggesting that investors prioritize tangible environmental outcomes over accounting disclosures when assessing a company's market worth. Keywords: Green Accounting, Environmental Performance, Company Value.